Awe experiences, the sublime, and spiritual well-being in Arctic wilderness - Løvoll, Helga Synnevåg; Sæther, Knut-Willy (Frontiers in Psychology, 2022)
Experiences of awe can carry the potential for life-transforming experiences and foster awareness of nature as a lifelong value. How these experiences emerge was investigated empirically in a pristine natural environment and analyzed informed by a bottom-up perspective with an interdisciplinary understanding of environmental aesthetics and positive psychology. A group of Arctic nature guide students (n = 34) were followed on an eight-day advanced glacier course with additional learning topics related to the arctic landscape and history, wildlife, and how to protect a wilderness camp from polar bear attacks. After this experience, students were invited to participate in the research project and were asked to reflect on their experiences immediately after their return to civilization. Two narratives each from 27 participants were collected, which provided 54 quotations for interpretation. Reflexive thematic analysis (RTA) surfaced three main themes: context, human response to encounters with nature, and transformation. The study of awe brings the tension between spirituality and well-being closer. The findings add empirical knowledge to understanding of the contexts for these highly affective and complex feelings. The findings also add refined knowledge about the relationship between awe and the sublime. In transformation for human well-being, the role of self-knowledge or self-transcendence surfaced by wilderness experiences should not be underestimated.